Nano-copper-containing high-temperature anti-sintering lubricating grease and preparation method thereof

The copper nanoparticles obtained through liquid phase reduction are used to develop high-temperature anti-sintering grease, which solves the wear and sintering problems in high-temperature environments, and realizes the high-temperature anti-sintering effect on automotive brake pads, high-temperature bolts and other components, which extends the The service life of the equipment.

CN119120087AInactive Publication Date: 2024-12-13安徽程冬科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411233803.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There is a lack of research on anti-sintering greases in high temperature environments in the prior art, especially in automobile brake pads, high temperature bolts and equipment with temperatures up to 1000°C, where wear and sintering problems exist, which are difficult to effectively solve.

Method used

Copper nanoparticles with uniform size were obtained by liquid phase reduction method and used as high-temperature resistant additives to develop a high-temperature anti-sintering grease containing nano copper, and a combination of thickening agents, base oils, antioxidants, and anti-rust Preservatives, extreme pressure anti-wear agents and nano-copper additives form greases that are resistant to high temperature and sintering.

Benefits of technology

The solid lubricating film is formed under high temperature conditions, which significantly reduces wear, prevents sintering, extends the service life of the equipment, and is suitable for automotive brake pads, high-temperature bolts and other components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119120087A_ABST
    Figure CN119120087A_ABST
Patent Text Reader

Abstract

The invention discloses high-temperature anti-sintering lubricating grease containing nano-copper. The high-temperature anti-sintering lubricating grease comprises 5-30% of a thickening agent, 60-80% of base oil, 0.1-2% of an antioxidant, 0.1-5% of an anti-rust preservative, 1-3% of an anti-wear reagent at extreme pressure and 10-20% of a nano-copper additive, according to the invention, the copper nano-particles with uniform size are obtained by a liquid phase reduction method, and the copper nano-material is used as a high-temperature-resistant additive, so that the nano-copper-based lubricating grease with high temperature resistance and sintering prevention is developed, and the nano-copper-based lubricating grease has very important application in automobile brake pads, high-temperature bolts and equipment with the temperature as high as 1000 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-temperature anti-sintering lubricating grease, and in particular to a high-temperature anti-sintering lubricating grease containing nano copper and a preparation method thereof. Background Art

[0002] Micro-nano copper powder has a wide range of applications in many fields, such as lubricants, catalysts, and heat conduction systems, due to its large specific surface area, strong surface activity, high melting point, good magnetic properties, electrical and thermal conductivity, and good light absorption.

[0003] During the driving process of the car, due to the harsh operating environment of the engine and the high internal temperature, friction and wear failure often occur, thus affecting the safety, reliability and service life of the equipment. The development and application of nanoparticle lubricating materials can effectively solve this problem to a certain extent. The nano copper powder is effectively dispersed in the lubricant through a certain method to form a stable suspension combined with the solid surface to form a protective layer, which will have a good friction reduction effect; filling scratches with nanoparticles can also greatly reduce wear, and the effect is obvious under low speed, heavy load and high temperature vibration conditions.

[0004] Currently, there are more reports on adding copper nanomaterials to lubricating oils. For example, nano copper particles are added to engine lubricating oil. After the engine has been running for a period of time, it is found that the copper nanoparticles form a deposition film on the surface of the connecting rod bearing, which effectively repairs the worn parts on the connecting rod bearing and produces a synergistic effect with the friction chemical reaction film formed by the surface modification layer, thereby showing good repair and anti-wear effects, which can extend the service life of the worn parts of the engine. However, there are few reports on research on nano copper-based grease.

[0005] The present invention provides a liquid phase reduction method to obtain copper nanoparticles of uniform size, and uses the copper nanomaterial as a high temperature resistant additive to develop a nano copper-based grease with high temperature resistance and anti-sintering properties, which has important applications in automobile brake pads, high temperature bolts, and equipment with temperatures as high as 1000°C. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art mentioned in the background technology, and to propose a high-temperature anti-sintering grease containing nano-copper and a preparation method thereof, wherein copper nanoparticles of uniform size are obtained by a liquid phase reduction method, and this copper nanomaterial is used as a high-temperature resistant additive to develop a nano-copper-based grease with high temperature resistance and anti-sintering properties, which has important applications in automotive brake pads, high-temperature bolts, and equipment with temperatures as high as 1000°C.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A nano copper-containing high-temperature anti-sintering grease comprises 5-30% of a thickener, 60-80% of a base oil, 0.1-2% of an antioxidant, 0.1-5% of an anti-rust and anti-corrosion agent, 1-3% of an extreme pressure and anti-wear agent, and 10-20% of a nano copper additive.

[0009] As a further feature of the method of the present invention, the thickener is a mixture of one or more of high-temperature thickener composite lithium, high-temperature thickener polyurea, and high-temperature thickener bentonite.

[0010] As a further feature of the method of the present invention, the base oil is a polyether synthetic oil, including a mixture of one or more of ethylene oxide, propylene oxide copolyether, propylene oxide polyether, copolyether containing tetrahydrofuran, and copolyether containing butylene oxide.

[0011] As a further feature of the method of the present invention, the kinematic viscosity of the base oil or the blended oil at 40°C is 50-400 mm2 / s.

[0012] As a further feature of the method of the present invention, the antioxidant comprises a mixture of one or more of phenolic antioxidants and amine antioxidants.

[0013] As a further feature of the method of the present invention, the rust and corrosion inhibitor comprises a mixture of one or more of benzotriazole, thiadiazole derivatives, sulfonates, carboxylic acids, carboxylic acid derivatives, organic phosphoric acids, organic amines, and heterocyclic compounds.

[0014] As a further feature of the method of the present invention, the extreme pressure anti-wear agent is a mixture of one or more of alkyl thioesters, sulfided olefins, organic phosphides, borates, and organic molybdenum salts.

[0015] As a further feature of the method of the present invention, the particle size of the nano copper additive is 200-300 nm, and the synthesis method thereof is as follows:

[0016] S1. Add 500 ml of water to a 1L three-necked flask, then add 19 g of cuprous oxide powder, 2 g of polyvinyl pyrrolidone, and 4 ml of ammonia water as a complexing agent and stir to mix at a stirring speed of 100-300 rpm;

[0017] S2, heat to 50-70°C, slowly add 20g of hydrazine hydrate aqueous solution to the mixed solution in S1;

[0018] S3, keeping warm for 1-2 hours, then washing with deionized water and ethanol, and drying in a vacuum drying oven to obtain nano copper powder.

[0019] As a further aspect of the method of the present invention, a method for preparing a high-temperature anti-sintering grease containing nano-copper comprises the following steps:

[0020] S1. Add 300g of polypropylene glycol ether base oil into a clean reactor, then add 25g of diphenylmethane diisocyanate, and heat to 60°C to dissolve;

[0021] S2. Take another clean container, slowly add 27g of octadecylamine and 100g of polypropylene glycol ether base oil, heat to 50-60°C to dissolve, then slowly add the octadecylamine oil solution to the listed reactor, and react at 80°C-100°C for 2h;

[0022] S3, when the temperature of the reactor is raised to 200°C, keep it warm for 10 minutes, add 200g of polypropylene glycol ether base oil and cool it;

[0023] S4. When the temperature drops to 80°C, add additives: 3g diphenylamine, 10g organic molybdenum, 60g nano copper powder, 1g T706, 2g T705, and grind 2-3 times to form fat.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] In the present invention, copper nanoparticles with uniform size are obtained by a liquid phase reduction method, and the copper nanomaterial is used as a high-temperature resistant additive and added to a specific grease. A solid lubricating film can be formed under high-temperature conditions, and the solid lubricating film has high-temperature resistant and anti-sintering functions, and can be used in automobile brake pads, high-temperature bolts, and equipment with temperatures as high as 1000°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of nano-copper in a high-temperature anti-sintering grease containing nano-copper and a preparation method thereof proposed by the present invention;

[0027] Figure 2 The present invention provides a high-temperature anti-sintering grease containing nano-copper and an XRD spectrum of nano-copper powder prepared in the preparation method thereof. DETAILED DESCRIPTION

[0028] The content of the present invention can be more easily understood by selecting the following detailed description of the preferred implementation method of the present invention and the embodiments included. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definition in this specification shall prevail.

[0029] As used herein, the term "prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0030] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0031] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.

[0032] Singular forms include plural references unless the context clearly indicates otherwise. "Optional" or "either" means that the subsequently described event or incident may or may not occur, and that the description includes instances where the event occurs and instances where it does not.

[0033] Approximate terms in the specification and claims are used to modify quantities, indicating that the present invention is not limited to the specific quantity, but also includes acceptable and modified parts close to the quantity without causing changes in the relevant basic functions. Accordingly, the use of "about", "approximately", etc. to modify a numerical value means that the present invention is not limited to the exact numerical value. In some examples, the approximate terms may correspond to the accuracy of the instrument for measuring the numerical value. In the specification and claims of this application, range limitations can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0034] In addition, the indefinite articles "a" and "an" before the elements or components of the present invention have no restrictions on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number is obviously intended to be in the singular form.

[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0036] Embodiment 1

[0037] A nano-copper-containing high-temperature anti-sintering grease comprises 5-30% thickener, 60-80% base oil, 0.1-2% antioxidant, 0.1-5% rust and corrosion inhibitor, 1-3% extreme pressure anti-wear agent, and 10-20% nano-copper additive; wherein the thickener is a high-temperature thickener such as composite lithium, polyurea, bentonite, etc.; the base oil is a polyether synthetic oil, including ethylene oxide, propylene oxide copolyether, propylene oxide polyether, copolyether containing tetrahydrofuran, copolyether containing butylene oxide, and their mixed oils; the kinematic viscosity of the base oil or the mixed oil at 40°C is 50-400mm2 / s, preferably the viscosity is 100-200mm2 / s; the antioxidant includes a phenolic antioxidant, an amine antioxidant or a mixture thereof, and the preferred antioxidants of the present invention are diphenylamine and 2,6-di-tert-butyl-p-cresol; the rust and corrosion inhibitors include a mixture of one or more of benzotriazole and thiadiazole derivatives, sulfonates, carboxylic acids and their derivatives, organic phosphoric acids and salts, organic amines, and heterocyclic compounds; the extreme pressure anti-wear agent is a mixture of one or more of alkyl thioesters, sulfonated olefins, organic phosphides, borates, organic molybdenum salts, etc.

[0038] Reference Figure 1-2 ,Depend on Figure 1 The results of scanning electron microscopy show that the prepared nano copper powder has good particle uniformity and a size between 200-300nm.

[0039] Figure 2 This is the XRD spectrum of the prepared copper powder, which corresponds perfectly to the standard card 04-0836 of Cu, indicating that there is no impurity peak and the synthesized nano copper powder is a pure substance.

[0040] The nano copper additive is homemade, and the particle size of the nano copper additive is 200-300nm (see Figure 1 ), and its synthesis method is as follows:

[0041] 1) Add 500 ml of water to a 1L three-necked flask, then add 19 g of cuprous oxide powder, 2 g of polyvinyl pyrrolidone, and 4 ml of ammonia water as a complexing agent, and start stirring at a speed of 100-300 rpm;

[0042] 2) Heat to 50-70°C, slowly add 20 g of hydrazine hydrate aqueous solution to the above solution;

[0043] 3) Keep warm for 1-2 hours, then wash with deionized water and ethanol, and dry in a vacuum drying oven to obtain nano copper powder (see Figure 1 ).

[0044] Embodiment 2

[0045] A method for preparing a high-temperature anti-sintering grease containing nano-copper, comprising the following steps:

[0046] 1) Add 300g of polypropylene glycol ether base oil into a clean reactor, then add 25g of diphenylmethane diisocyanate and heat to 60°C to dissolve;

[0047] 2) In another clean container, slowly add 27g of octadecylamine and 100g of polypropylene glycol ether base oil, heat to 50-60°C to dissolve, then slowly add the octadecylamine oil solution to the commercial reactor, and react at 80°C-100°C for 2h;

[0048] 3) When the temperature of the reactor is raised to 200°C, keep it warm for 10 minutes, add 200g of polypropylene glycol ether base oil and cool it;

[0049] 4) When the temperature drops to 80°C, add additives 3g diphenylamine, 10g organic molybdenum, 60g nano copper powder, 1g T706, and 2g T705, grind 2-3 times to form fat, and its properties are shown in Table 1.

[0050] Embodiment 3

[0051] A method for preparing a high-temperature anti-sintering grease containing nano-copper, comprising the following steps:

[0052] 1) Add 500g of polyglycol ether base oil, 20g of bentonite, and then 10g of ethanol dispersant into a clean reactor, heat to 60°C, and react for 30 minutes;

[0053] 2) gradually heating to 100°C and reacting for 2h;

[0054] 3) When the temperature of the reactor is raised to 200°C, keep it warm for 10 minutes, add 300g of polypropylene glycol ether base oil and cool it;

[0055] 4) When the temperature drops to 80°C, add 5g of additives, diphenylamine, 10g of organic molybdenum, 150g of nano copper powder, 3g of T706, and 3g of T705, grind 2-3 times to form fat. Its properties are shown in Table 1.

[0056]

[0057]

[0058] The examples referred to herein are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to claim the widest possible range that can be imagined, and the embodiments presented herein are only illustrations of selected implementations according to the combination of all possible embodiments. Therefore, it is the applicant's intention that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges within them, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.

Claims

1. A high-temperature anti-sintering grease containing nano-copper, characterized in that: The invention comprises 5-30% of thickener, 60-80% of base oil, 0.1-2% of antioxidant, 0.1-5% of anti-rust and anti-corrosion agent, 1-3% of extreme pressure and anti-wear agent and 10-20% of nano copper additive.

2. A high-temperature anti-sintering grease containing nano-copper according to claim 1, characterized in that: The thickener is a mixture of one or more of high-temperature thickener composite lithium, high-temperature thickener polyurea, and high-temperature thickener bentonite.

3. The high-temperature anti-sintering grease containing nano-copper according to claim 1, characterized in that: The base oil is a polyether synthetic oil, including a mixture of one or more of ethylene oxide, propylene oxide copolyether, propylene oxide polyether, copolyether containing tetrahydrofuran, and copolyether containing butylene oxide.

4. A high-temperature anti-sintering grease containing nano-copper according to claim 3, characterized in that: The kinematic viscosity of the base oil or blended oil at 40°C is 50-400mm2 / s.

5. The high-temperature anti-sintering grease containing nano-copper according to claim 1, characterized in that: The antioxidant comprises a mixture of one or more of a phenolic antioxidant and an amine antioxidant.

6. According to the high-temperature anti-sintering grease containing nano-copper in claim 1, the rust and corrosion inhibitor comprises a mixture of one or more of benzotriazole, thiadiazole derivatives, sulfonates, carboxylic acids, carboxylic acid derivatives, organic phosphoric acids, organic amines, and heterocyclic compounds.

7. According to the nano-copper-containing high-temperature anti-sintering grease of claim 1, the extreme pressure anti-wear agent is a mixture of one or more of alkyl thioesters, sulfided olefins, organic phosphides, borates, and organic molybdenum salts.

8. According to claim 1, a high-temperature anti-sintering grease containing nano-copper, the particle size of the nano-copper additive is 200-300nm, and the synthesis method thereof is as follows: S1. Add 500 ml of water to a 1L three-necked flask, then add 19 g of cuprous oxide powder, 2 g of polyvinyl pyrrolidone, and 4 ml of ammonia water as a complexing agent and stir to mix at a stirring speed of 100-300 rpm; S2, heat to 50-70°C, slowly add 20g of hydrazine hydrate aqueous solution to the mixed solution in S1; S3, keeping warm for 1-2 hours, then washing with deionized water and ethanol, and drying in a vacuum drying oven to obtain nano copper powder.

9. The method for preparing a high-temperature anti-sintering grease containing nano-copper according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Add 300g of polypropylene glycol ether base oil into a clean reactor, then add 25g of diphenylmethane diisocyanate, and heat to 60°C to dissolve; S2. Take another clean container, slowly add 27g of octadecylamine and 100g of polypropylene glycol ether base oil, heat to 50-60°C to dissolve, then slowly add the octadecylamine oil solution to the listed reactor, and react at 80°C-100°C for 2h; S3, when the temperature of the reactor is raised to 200°C, keep it warm for 10 minutes, add 200g of polypropylene glycol ether base oil and cool it; S4. When the temperature drops to 80°C, add additives: 3g diphenylamine, 10g organic molybdenum, 60g nano copper powder, 1g T706, 2g T705, and grind 2-3 times to form fat.